MiR-4646-5p Acts as a Tumor-Suppressive Factor in Triple Negative Breast Cancer and Targets the Cholesterol Transport Protein GRAMD1B - Jonas, Katharina; Prinz, Felix; Ferracin, Manuela; Krajina, Katarina; Deutsch, Alexander; Madl, Tobias; Rinner, Beate; Slaby, Ondrej; Klec, Christiane; Pichler, Martin (Non-coding RNA, 2023)
MicroRNAs (miRNAs) are crucial post-transcriptional regulators of gene expression, and their deregulation contributes to many aspects of cancer development and progression. Thus, miRNAs provide insight into oncogenic mechanisms and represent promising targets for new therapeutic approaches. A type of cancer that is still in urgent need of improved treatment options is triple negative breast cancer (TNBC). Therefore, we aimed to characterize a novel miRNA with a potential role in TNBC. Based on a previous study, we selected miR-4646-5p, a miRNA with a still unknown function in breast cancer. We discovered that higher expression of miR-4646-5p in TNBC patients is associated with better survival. In vitro assays showed that miR-4646-5p overexpression reduces growth, proliferation, and migration of TNBC cell lines, whereas inhibition had the opposite effect. Furthermore, we found that miR-4646-5p inhibits the tube formation ability of endothelial cells, which may indicate anti-angiogenic properties. By whole transcriptome analysis, we not only observed that miR-4646-5p downregulates many oncogenic factors, like tumor-promoting cytokines and migration- and invasion-related genes, but were also able to identify a direct target, the GRAM domain-containing protein 1B (GRAMD1B). GRAMD1B is involved in cellular cholesterol transport and its knockdown phenocopied the growth-reducing effects of miR-4646-5p. We thus conclude that GRAMD1B may partly contribute to the diverse tumor-suppressive effects of miR-4646-5p in TNBC.
Keywords: microRNA (miRNA); GRAM domain-containing protein 1B (GRAMD1B); triple negative breast cancer (TNBC); cholesterol transport protein